2004
DOI: 10.1086/382939
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption Signatures of Dwarf Galaxies: Thez = 1.04 Multicloud Weak MgiiAbsorber toward PG 1634+706

Abstract: We analyze high-resolution spectra of a multicloud weak [defined as W r Mg ð iiÞ < 0:3 8] absorbing system along the line of sight to PG 1634+706. This system gives rise to a partial Lyman limit break and absorption in Mg ii, Si ii, C ii, Si iii, Si iv, C iv, and O vi. The lower ionization transitions arise in two kinematic subsystems with a separation of '150 km s À1 . Each subsystem is resolved into several narrow components having Doppler widths of 3-10 km s À1 . For both subsystems, the O vi absorption ari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 52 publications
(102 reference statements)
5
68
0
Order By: Relevance
“…However, the actual χ 2 -value is often spoiled by a few pixels that are contaminated by problems with the noise array or simply line blends (formerly noticed also by e.g. Charlton et al 2003;Ding et al 2003a,b;Zonak et al 2004). Even though we try to minimize the influence of bad pixel on the χ 2 by selecting the lines and intervals appropriate to be used for each system individually, a visual inspection is needed.…”
Section: Modelling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual χ 2 -value is often spoiled by a few pixels that are contaminated by problems with the noise array or simply line blends (formerly noticed also by e.g. Charlton et al 2003;Ding et al 2003a,b;Zonak et al 2004). Even though we try to minimize the influence of bad pixel on the χ 2 by selecting the lines and intervals appropriate to be used for each system individually, a visual inspection is needed.…”
Section: Modelling Proceduresmentioning
confidence: 99%
“…in Charlton et al 2003;Ding et al 2003aDing et al ,b, 2005Zonak et al 2004;Masiero et al 2005). Especially O vi is believed to arise in a spatially more extended, low density gas (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…However, it was not until the STIS spectrograph on HST provided high resolution UV spectra of absorption kinematics from a wide range of ionisation species, such as Siii, Siiv, Cii, Ciii, Civ, Nii, Nv, O vi, and neutral hydrogen, that multiphase photoionisation could be modelled in detail Ding et al 2003;Zonak et al 2004;Masiero et al 2005;.…”
Section: Modelling and Ionisation Conditionsmentioning
confidence: 99%
“…Some weak absorbers have multiple "clouds" spread over 10-100 km s −1 , but most are single clouds. It has been suggested that these systems are associated with low surface brightness galaxies (Churchill & Le Brun 1997), intergalactic star forming "pockets" (Rigby et al 2002), or dwarf galaxies (Zonak et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…At the time of the Ribaudo et al (2011b) study, there were only about 8 metallicity estimates in LLSs (see, e.g., Lehner et al 2009;Cooksey et al 2008;Zonak et al 2004;Tripp et al 2011) and about 50% of those had [X/H] −1.5. This is remarkable because as I will show below the sample of pLLSs and LLSs has increased by factors 3.5 and now 7 and yet the same fraction of very metal-poor gas has been found for the combined sample of pLLSs and LLSs.…”
Section: Metallicity: Methodology and Uncertaintiesmentioning
confidence: 99%